LEXICAL COHESION IN NEWS ARTICLE ON THE JAKARTA POST ENTITLED “WHY FULL DAY SCHOOL WILL NOT WORK IN INDONESIA?” - Puspita, Galih Setia; Khairun Nisa, Farida Rizkiyah; Suprijadi, Dasep (PROJECT (Professional Journal of English Education), 2019)
The purpose of this study is to investigate what types and what is mostly found of lexical cohesion in the news article. Written texts are different from spoken interaction. To make the readers know what the writers mean, the writers should compose a well formed of the text. Cohesion is an aspect of a text, which entails that the letter forms a unified whole, rather than unrelated sentences. Cohesion plays a special role in the creation of text. There are two main types of cohesion there are grammatical cohesion and lexical cohesion. Grammatical cohesion consist of reference, ellipsis, substitution and conjunction, whereas lexical cohesion has two aspects, they are reiteration and collocation. Lexical cohesion refers to the way related words are chosen to link elements of a text. This study used qualitative research as the research method. Based on the result of this study, it can be concluded that there are six types of lexical cohesion and the types of lexical cohesion which is mostly used by the writer is repetition but this article is lack of antonym. And the use of lexical cohesion in writing a text can deliver the meaning of whole text itself for the readers easily and clearly.